1998
DOI: 10.1042/bj3360241
|View full text |Cite
|
Sign up to set email alerts
|

The activation of protein kinase B by H2O2 or heat shock is mediated by phosphoinositide 3-kinase and not by mitogen-activated protein kinase-activated protein kinase-2

Abstract: Protein kinase B (PKB) isoforms became activated [and glycogen synthase kinase-3 (GSK3) became inhibited] when mouse Swiss 3T3 fibroblasts were exposed to oxidative stress (H2O2) or heat shock, but not when they were exposed to osmotic shock (0.5 M sorbitol or 0. 7 M NaCl), chemical stress (sodium arsenite), the protein-synthesis inhibitor anisomycin, or UV radiation. In contrast, all seven stimuli activated mitogen-activated protein kinase-activated protein kinase-2 (MAPKAP-K2). The activation of MAPKAP-K2 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
188
3
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(214 citation statements)
references
References 31 publications
22
188
3
1
Order By: Relevance
“…Based on data showing that PI3K inhibitors do not prevent AKT1 activation by stress, these studies concluded that stressinduced AKT1 activation was PI3K-independent. Other studies, however, found that PI3K activity was required for AKT1 activation by heat shock or oxidative stress in Swiss 3T3 cells (19,20). It has been suggested that certain cellular stresses activate AKT1 and AKT3 but not AKT2 (19), a finding that is consistent with the different functions of the AKTs as revealed by studies of mice lacking AKT1 or AKT2 (21)(22)(23).…”
mentioning
confidence: 64%
“…Based on data showing that PI3K inhibitors do not prevent AKT1 activation by stress, these studies concluded that stressinduced AKT1 activation was PI3K-independent. Other studies, however, found that PI3K activity was required for AKT1 activation by heat shock or oxidative stress in Swiss 3T3 cells (19,20). It has been suggested that certain cellular stresses activate AKT1 and AKT3 but not AKT2 (19), a finding that is consistent with the different functions of the AKTs as revealed by studies of mice lacking AKT1 or AKT2 (21)(22)(23).…”
mentioning
confidence: 64%
“…Although cell-type differences may explain such discrepancy, the ability of sorbitol to increase PKB activity in fibroblasts has not been consistently observed. 25,27 This could be explained by the fact that sorbitol is a weak activator of PKB making this effect difficult to detect. Our results clearly show that PKB activity is increased by sorbitol in fibroblasts (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the activity of PI-3 kinase, the level of 3-phosphorylated PIs, and the activity of Akt are increased in cells exposed to H 2 O 2 (Konishi et al, 1997;Shaw et al, 1998;Sonoda et al, 1999;Tanaka et al, 1999;Qin et al, 2000). This H 2 O 2 -mediated activation of PI-3 kinase/Akt pathway is considered to be the result of reversible oxidation and inactivation of protein tyrosine phosphatase (PTP) family protein such as PTEN that have a critical cysteine residue in the active site (Denu and Tanner, 1998;Lee et al, 1998;Meng et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because PTEN has a critical role in antagonizing PI-3 kinase signaling pathways, it might be expected that PTEN would be the target of complex control mechanisms. Only limited studies have addressed this issue, but evidence is now emerging for functional regulation of PTEN at the level of protein stability and localization, as well as transcription of the PTEN gene (Adey et al, 2000;Vazquez et al, 2000Vazquez et al, , 2001Kurose et al, 2001;Bastola et al, 2002).It has been demonstrated that the activity of PI-3 kinase, the level of 3-phosphorylated PIs, and the activity of Akt are increased in cells exposed to H 2 O 2 (Konishi et al, 1997;Shaw et al, 1998;Sonoda et al, 1999;Tanaka et al, 1999;Qin et al, 2000). This H 2 O 2 -mediated activation of PI-3 kinase/Akt pathway is considered to be the result of reversible oxidation and inactivation of protein tyrosine phosphatase (PTP) family protein such as PTEN that have a critical cysteine residue in the active site (Denu and Tanner, 1998;Lee et al, 1998;Meng et al, 2002).…”
mentioning
confidence: 99%